2004
DOI: 10.1111/j.0956-7976.2004.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

When Children Ask, “What Is It?” What Do They Want to Know About Artifacts?

Abstract: When children ask, "What is it?" are they seeking information about what something is called or what kind of thing it is? To find out, we gave 2-, 3-, and 4-year-olds (32 at each age) the opportunity to inquire about unfamiliar artifacts. An ambiguous question was answered with a name or with functional information, depending on the group to which the children were assigned. Children were inclined to follow up with additional questions about the object when they had been told its name, but seemed satisfied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Although children sometimes show remarkable and appropriate skepticism, we must be careful not to overstate young children’s ability to detect reasons to doubt, as doing so may inadvertently put them in harm’s way. That said, we also must recognize that children do have a strong desire to fully understand the world around them (e.g., Gopnik, 1998), being unsatisfied with incomplete or wrong answers to their questions (e.g., Frazier, Gelman, & Wellman, 2009; Kemler Nelson, Egan, & Holt, 2004). Thus, even young children show a clear desire to discover the truth.…”
Section: Discussionmentioning
confidence: 99%
“…Although children sometimes show remarkable and appropriate skepticism, we must be careful not to overstate young children’s ability to detect reasons to doubt, as doing so may inadvertently put them in harm’s way. That said, we also must recognize that children do have a strong desire to fully understand the world around them (e.g., Gopnik, 1998), being unsatisfied with incomplete or wrong answers to their questions (e.g., Frazier, Gelman, & Wellman, 2009; Kemler Nelson, Egan, & Holt, 2004). Thus, even young children show a clear desire to discover the truth.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains to be seen whether children have more fine-tuned expectations. For example, previous research has shown that object function is viewed as a central aspect of artifact concepts even for young children (Bloom, 1996; Greif, Kemler Nelson, Keil, & Gutierrez, 2006; Kemler Nelson, Egan, & Holt, 2004) and that children expect objects of the same kind to share functional features (Davidson & Gelman, 1990; Gelman, 1988; Welder & Graham, 2001; Gelman, 1988). Thus, children may view object function as a feature that is particularly likely to be homogeneous in artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…One study systematically explored children's reactions to responses given to the child's "What is it?" questions about a novel artifact (Kemler Nelson, Chan, & Holt, 2004). Children were more likely to ask follow-up questions when they received an object label than when given the object's function.…”
mentioning
confidence: 99%